2014
DOI: 10.1007/s10803-014-2283-7
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Behavior in Rubinstein–Taybi Syndrome: Parallels with Autism Spectrum Phenomenology

Abstract: R e p e t i t i v e b e h a v i o u r i n R u b i n s t e i n -T a y b i s y n d r om e : P a r a l l e l s w i t h a u t i sm s p e c t r um p h e n om e n o l o g y J a n e W a i t e , J o a n n a M o s s , S a r a h B e c k , C a r o l i n e R i c h a r d s , L i s a N e l s o n , K a t e A r r o n , C h e r y l B u r b i d g e , K a t y B e r g a n d C h r i s O l i v e r C e r e b r a C e n t r e f o r N e u r o d e v e l o pm e n t a l D i s o r d e r s , S c h o o l o f P s y c h o l o g y , U n i v e r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 51 publications
2
50
0
Order By: Relevance
“…Furthermore, 40% of the sample showed a diverse profile of repetitive motor movements (such as swinging and turning on themselves), which included elevated levels of stereotyped behaviors as described in the literature (Waite et al, ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, 40% of the sample showed a diverse profile of repetitive motor movements (such as swinging and turning on themselves), which included elevated levels of stereotyped behaviors as described in the literature (Waite et al, ).…”
Section: Resultsmentioning
confidence: 93%
“…A short attention span is described in 90% of individuals (Galéra et al, ; Stevens et al, ). Galerà et al reported high rates of repetitive motor movement and some autistic‐like behavior patterns; more recently, Waite et al () confirmed a heterogeneous profile of repetitive behaviors (e.g., body stereotypies and repetitive questions).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Language items not suitable for non-verbal children can be omitted; it is scored according to language level (maximum score 32 or 39), with higher scores indicating more severe symptoms. Five studies have used the SCQ to characterize autistic behavior and its severity in FXS [141, 169–172]. However, none has examined measurement properties including sensitivity.…”
Section: Behavior and Emotion Measuresmentioning
confidence: 99%
“…RRB are one of the core diagnostic features of ASD, however, they are not specific to ASD but are also prevalent across a range of other disorders and genetic syndromes [Moss, Oliver, Arron, Burbridge, & Berg, ] where they cannot be fully accounted for by either the potential presence of ASD or intellectual disability [Janes, Riby, & Rodgers, ; Rodgers, Riby, Janes, Connolly, & McConachie, ; Waite et al, ]. Importantly, RRB also occur in young typically developing children [Arnott et al, ; Evans et al, ; Leekam et al, ; Uljarević et al, ].…”
Section: Introductionmentioning
confidence: 99%